Freedom In Dostoevsky's Brothers Karamazov: An Existentialism Approach - Mayasari, Mayasari (2004)
This research paper deals with Freedom as a basic premises of existence. The object of this study is Dostoevsky's Brothers Karamazov. This study deals with human's free will as reflected in Dostoevsky's Brothers Karamazov. This study aims at describing the structural elements of the novel and exposing the ideas of free will in the novel based on Kierkegaard's existentialism. The benefit of this study is to give some contribution to the English Literary studies particularly the application of existentialism. Type of qualitative of research, the method of data collection is library research and the technique of data analysis is descriptive. Kierkegaard's philosophy of existentialism is used as an apprehension to analyze the novel. The outcomes of the study are as follow: first, literature serves as an instrument for the author to convey his philosophical view. Second, according to Dostoevsky freedom can be implemented in two different ways; freedom that kills life and freedom that gives life. Third, freedom must be implemented with limitation otherwise unlimited freedom will create crime.